The environmental mining liabilities and social conflicts in Hualgayoc - Pinto Herrera, Honori (2013)
The paper deals with the mining environmental liabilities (PAM) and the social conflicts of Hualgayoc (Cajamarca) whose attention has been considered a priority by the Ministry of Energy and Mines (MEM). Contains number of PAM, a historical description of this mining center, a brief chronology that presents the efforts of the MEM and FONAM to achieve the remediation of the PAM, finally the facts set forth structural and cyclical that prevent the full remediation of the PAM in Hualgayoc, problem with they will be living the inhabitants of this province for many years. And that will be a constant threat of future social conflict.